THE EFFECT OF PREGNANCY EXERCISES ON REDUCING LOWER BACK PAIN IN III TRIMESTER PREGNANT WOMEN AT BUMI BARU PUSKESMAS - Almufaridin, Anissa Syafitri; Mahdalyanti; Yunfindi Sari, Nefi; Sundari, Neti (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Pregnancy is a process that starts from the conception stage until the birth of the fetus, which lasts for 40 weeks starting from the first day of the last menstruation. When the fetus grows in the womb there will be changes that occur in the mother's body, these changes will cause discomfort such as back pain. This type of research is a quasi-experimental research with a prepost test design with one group test. The number of samples used was 28 pregnant women at Bumi Baru Community Health Centers obtained using the total sampling technique. The data analysis technique uses the Paired-T Test. The results obtained in this study were that before being given pregnancy exercise, 1 person (3.83%) experienced very severe pain, 8 (30.7%) had moderate pain, 7 (26.92%) had moderate pain and 10 people (38) had mild pain. .46%). After being given pregnancy exercises, no one experienced very severe or severe pain, moderate pain was reduced to 2 people (7.69%), mild pain to 14 people (53.84%) and no pain to 10 people (38.46%) , and there were 10 people (33.3%) who no longer felt pain. The average pain level obtained before pregnancy exercise was 5.69 and after pregnancy exercise was 2.23, resulting in a decrease of 3.46 and this decrease was significant with a p value of 0.000.